The Impact of TikTok Shop’s Perceived Service Quality and Electronic Word of Mouth on the Purchase Intention of University Students - Mendoza, Enrico C.; Evangelista, Ysabella O.; Gan, Aaliyah A.; Mayuga, Adrian C.; Reyes, Joaquin B. (International Review of Management and Marketing, 2026)
This study investigates the impact of TikTok Shop’s perceived service quality and electronic word of mouth (e-WOM) on the purchase intentions of undergraduate students at De La Salle University Manila. As TikTok transitions from a social media platform to a key player in social commerce, understanding how its features influence consumer behavior has become crucial. Guided by the SERVQUAL model and e-WOM framework, this research explores how service quality dimensions tangibility, reliability, responsiveness, assurance, and empathy along with e-WOM factors such as message quality and platform credibility, affect students’ likelihood to purchase through TikTok Shop.Using a quantitative research design, data were collected from DLSU undergraduate students who had previously made purchases on the platform. Statistical analyses including descriptive statistics, Pearson correlation, and multiple linear regression were employed to determine the strength and significance of relationships among the variables. Findings reveal that all five SERVQUAL dimensions and key e-WOM factors significantly influence purchase intention. Notably, assurance and platform credibility emerged as the strongest predictors, emphasizing the importance of trust and secure transaction environments. The results underscore the necessity for sellers and platform managers to enhance service responsiveness. This study is valuable for marketers, businesses, and policymakers seeking to optimize consumer engagement on social commerce platforms. It also fills both theoretical and methodological gaps in the literature by applying traditional service quality and behavioral theories to a dynamic, algorithm driven social commerce environment like TikTok Shop.